Promoting education for sustainable consumption and production: an analysis of Malaysian school curriculum - Tee, Lian Hong; Abdullah, Sabrina J. Ho; Mohd Noah, Sidek (Babes-Bolyai University, 2019)
This paper provides understanding of education of sustainable consumption and production (ESCP) and its implementation, Education for Sustainable Consumption (ESC) and Education for Sustainable Development (ESD). These are the driving tools to address the challenges of sustainable consumptions such as environmental degradation, depletion of natural resources, pollutions, global warming and poverty that negatively affect the quality of life. Therefore, the practical approach to promote ESCP was presenting its purpose and its potential to positively affect the education system. The objective of this study is to assess the existing initiatives in ESCP for Malaysian public education system. The document analysis method was conducted towards the secondary public school for their curriculum materials and textbooks. The result from the analysis shows that some of the elements in the content are related to sustainable consumption and production of education. One of the learning outcomes was that it matches the desired behavioral of sustainable consumption. It is concluded that education plays a vital role in strengthening the sustainable consumption choice and it is evidently supported by government policy as stated in The National Sustainable Consumption and Production Blueprint 2016-2030. The integration of ESCP into curriculum is indisputably important to facilitate and provide adequate transformation for the sustainable consumption behavior into daily life practice.